The Effects of Learning Strategies and Learning Styles on Learning Outcomes of Basic Physics - Kasmiati, Sitti; Priyono,; Ibrahim, Nurdin (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of learning strategies and learning styles on learning outcomes of Basic Physics from Physics Department Students at FKIP Halu Oleo University, while the learning strategies provided in the experimental class are inquiry learning strategies. This research was conducted on students majoring in physics at the faculty of education and education at Halu Oleo University which lasted eight meetings. In this study the data were obtained by giving a test of learning outcomes to 94 students. The research method used was a quasi-experimental method with a 2x2 design. Data were analyzed using two-way ANOVA. The results showed that there were differences in student learning outcomes between those learned using inquiry learning strategies and those learned using direct learning, the average Basic Physics learning outcomes learned with inquiry learning strategies were higher compared to the average learning outcomes of Basic Physics students who were learned with use direct learning strategies, learning styles affect student learning outcomes Basic Physics; there is an interaction between learning strategies, learning styles and learning outcomes in Basic Physics